Analisis Kinerja Finansial Koperasi Karta Jaya Kembang Besar Desa Tabihi Kecamatan Padang Batung Kabupaten Hulu Sungai Selatan - Ratih Noviartie; Eka Radiah; Kamiliah Wilda (AGRIDES: Jurnal Agribisnis Perdesaan, 2014)
The study is purposed: (1) to assess the community satisfaction on CSR program supporled by Adara; and (2) to excavate the community expectation on the program. The study site was Kecamatan Paringin - Kabupaten Balangan and 82 respondents were involved. The Importance Performance Analysis was used to measure the variables or attributes, so the importance and perforce level can be determined to develop further CSR program. According to the community opinion, the responsibility to develop the community is the most important attribute (4.26), while the suitability is less important. The score of community participation on the program proposal and planning is 3.44. The highest performance level is the need of suitability (3.37), while the community participation in proposing activities is the lowest (2. 60). The community expects that the program should be accompanied by professional adviser to guide them in implementing aff activities.